White blood cell count and risk of incident lung cancer in the UK Biobank - Wong,JYY; Bassig,BA; Loftfield,E; Hu,W; Freedman,ND; Ji,B-T; Elliott,P; Silverman,DT; Chanock,SJ; Rothman,N; Lan,Q (JNCI Cancer Spectrum, 2019)
BackgroundThe contribution of measurable immunological/inflammatory parameters to lung cancer development remains unclear, particularly among never-smokers. We investigated the relationship between total and differential white blood cell (WBC) counts and incident lung cancer risk overall and among subgroups defined by smoking status and sex in the United Kingdom (UK).MethodsWe evaluated 424,407 adults aged 37-73 years from the UK Biobank. Questionnaires, physical measurements, and blood were administered/collected at baseline in 2006-2010. Complete blood cell counts were measured using standard methods. Lung cancer diagnoses and histological classifications were obtained from cancer registries. Multivariable Cox regression models were used to estimate the hazard ratio (HR) and 95% confidence intervals (CI) of incident lung cancer in relation to quartiles (Q) of total WBC and subtype-specific counts, with Q1 as the reference.ResultsThere were 1,493 incident cases diagnosed over an average 7-year follow-up. Overall, the highest quartile of total WBC count was significantly associated with elevated lung cancer risk (HRQ4=1.67, 95% CI:1.41-1.98). Among women, increased risks were found in current-smokers (ncases/n=244/19,464, HRQ4=2.15, 95% CI:1.46-3.16), former-smokers (ncases/n=280/69,198, HRQ4=1.75, 95% CI:1.24-2.47), and never-smokers without environmental tobacco smoke exposure (ncases/n=108/111,294, HRQ4=1.93, 95% CI:1.11-3.35). Among men, stronger associations were identified in current-smokers (ncases/n=329/22,934, HRQ4=2.95, 95% CI:2.04-4.26) and former-smokers (ncases/n= 358/71,616, HRQ4=2.38, 95% CI:1.74-3.27) but not in never-smokers. Findings were similar for lung adenocarcinoma and squamous cell carcinoma and were driven primarily by elevated neutrophil fractions.ConclusionsElevated WBCs could potentially be one of many important markers for increased lung cancer risk, especially among never-smoking women and ever-smoking men.